FISHES AT RISK: UNVEILING THE HIDDEN DIVERSITY OF A VULNERABLE LAKE IN THE PERUVIAN AMAZON REGION - RUIZ-TAFUR, Kevin Morgan (2023)
The study focuses on the Huachana lake, a vulnerable ecosystem in the Peruvian Amazon region that receives wastewater from the city of Iquitos. Despite its significance in ichthyology and its role as a type locality for various species, water bodies near Iquitos face threats. While a portion of the ichthyological diversity in the Loreto region is known, the Huachana lake had never been subject to sampling, making this study the first to examine fish diversity in this aquatic environment. A total of 52 fish species from 5 orders, 20 families, and 39 genera were identified. The Characiformes present the greatest species richness (30 species), followed by Cichliformes (12 species). Cichlidae and Characidae are the families richest in species. No species are endangered according to the IUCN; the majority are considered of least concern. The study also identified ornamental and commercial species, providing crucial information about ichthyofauna in nearby urban areas and its potential long-term environmental impact.